2003
DOI: 10.1097/01.ccm.0000057911.19145.9f
|View full text |Cite
|
Sign up to set email alerts
|

Role of exogenous surfactant in acute lung injury

Abstract: Exogenous surfactant administration has proven inconsistent as a therapeutic modality for patients with acute respiratory distress syndrome. This is because of the severity of the injury at the time of treatment and because of the variable surfactant preparations, dosing regimes, and delivery methods used in the different trials. Future research efforts will focus on determining the optimal timing of surfactant administration in patients at risk of developing acute respiratory distress syndrome with the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 27 publications
0
33
0
2
Order By: Relevance
“…Major mechanisms of surfactant inactivation in ARDS include decreased synthesis and secretion of surfactant by the type II pneumocytes, decrease in surface active small aggregates of surfactant in the alveoli, and direct inhibition of surfactant function by substances like meconium, blood, serum proteins or proteinaceous edema fluid. 37 Exogenous surfactant therapy has been shown to be beneficial 70% of the time in patients with ARDS. 38 In a randomized, controlled trial using beractant in forty newborns with MAS, Findley et al 39 demonstrated a significant reduction in the need for extracorporeal membrane oxygenation (ECMO) therapy.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%
“…Major mechanisms of surfactant inactivation in ARDS include decreased synthesis and secretion of surfactant by the type II pneumocytes, decrease in surface active small aggregates of surfactant in the alveoli, and direct inhibition of surfactant function by substances like meconium, blood, serum proteins or proteinaceous edema fluid. 37 Exogenous surfactant therapy has been shown to be beneficial 70% of the time in patients with ARDS. 38 In a randomized, controlled trial using beractant in forty newborns with MAS, Findley et al 39 demonstrated a significant reduction in the need for extracorporeal membrane oxygenation (ECMO) therapy.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%
“…(1-4) Among the various strategies used to fight ARDS, treatment with exogenous surfactant is supported by the strongest experimental evidence: in many animal models of ARDS, (5)(6)(7)(8)(9) and in children with ARDS, (1,4,(10)(11)(12) it is clearly evident that synthesis of surfactant is decreased while surfactant inactivation and consumption is increased. The alveoli of ARDS children show a lack of surfactant active forms (large aggregates) and an increase in small aggregates that are the catabolic products of surfactant and are functionally inactive.…”
Section: Introductionmentioning
confidence: 96%
“…The alveoli of ARDS children show a lack of surfactant active forms (large aggregates) and an increase in small aggregates that are the catabolic products of surfactant and are functionally inactive. (4) This impairment in surfactant function is closely associated with alterations in pulmonary function that characterize children with ARDS. (4) Although in animal models the administration of exogenous surfactant is able to change the course of ARDS, when it is studied in children its beneficial effect is weak or totally absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALI results from a variety of insults as diverse as meconium aspiration in newborns, hydrochloric acid reflux, sepsis, and ventilator trauma. In turn, injury predisposes the patient to acute (or adult) respiratory distress syndrome (ARDS) (1)(2)(3)(4). Pulmonary surfactant replacement, now a mainstay in the treatment of respiratory distress syndrome in premature infants, has not enjoyed comparable success in treating ARDS (5)(6)(7).…”
mentioning
confidence: 99%